Irrigation-coupled bipolar cautery unit: A practical, economical, and simple version - Sharma Shekhar; Haji Altaf; Vijaykumar D; Shaji A (Indian Journal of Plastic Surgery, 2008)
Hemostasis is a fundamental principle of surgery for which electrocoagulation is universally used. Bipolar electrocautery has an advantage over monopolar electrocautery in terms of the precision of the extent of tissue coagulation and the lateral extent of thermal tissue injury. However, secondary to the thermal changes induced in the tissue due to electric current passage, there is charring of tissue, which adheres to the cautery tip. This, not only decreases its effectiveness, but also, by getting avulsed while removing the cautery tip from the surgical field, causes rebleeding and more trauma to the tissue. Irrigation of the surgical field during application of cautery reduces the charring effect, thereby improving the efficiency and efficacy. Irrigation-coupled electrocautery devices are available but are costly to acquire and maintain. We describe a simple and reliable version of an irrigation-coupled cautery device, which is of immense functional utility in our experience. It decreases the amount of charring of the tissue and its adherence to the bipolar forceps tips, thereby decreasing the frustrating loss of effectiveness and also increases the life of the bipolar forceps as cleaning needs to be less frequent. By virtue of its simplicity and cost-effectiveness, it can be used in almost all hospitals and situations.